Islamic Law and Its Role in Regulating Muslim Society - Abdul Farid (Edujavare Publishing, 2026)
This study examines the role of Islamic law in regulating Muslim society in the contemporary era. The research aims to analyze how Islamic legal principles function as a comprehensive system that integrates legal, ethical, and spiritual dimensions in guiding social, economic, and family life. A normative legal research method is applied using conceptual, doctrinal, and analytical approaches based on secondary legal sources, including classical Islamic texts, contemporary scholarly works, and institutional reports. The findings show that Islamic law plays a central role in shaping social order through principles of justice, welfare, and harm prevention. It regulates key areas such as family relations, economic transactions, and social welfare mechanisms while remaining adaptable through ijtihad and legal interpretation. However, challenges such as interpretative diversity and modern legal pluralism affect its implementation. The study concludes that Islamic law remains a dynamic and relevant legal system for regulating Muslim society in the modern era.